Incorporation of ESG criteria in the activities of companies in the context of their investment screening - I.O. (Економіка, управління та адміністрування)
This article examines the concept of integrated sustainability management and its relationship with corporate social responsibility (CSR) and environmental, social and corporate governance (ESG). Although CSR is a normative concept that requires companies to be responsible for their participation in society from an ethical perspective, ESG helps measure and quantify these efforts, primarily through investment criteria. The paper identifies that sustainability reporting (SDR) can bring financial, reputational, risk management and strategic benefits to companies, and more companies recognize the importance of sustainability reporting and making it a priority in their business practices. This study presented grouped classifications of the benefits of ESG disclosure in corporate reporting. The main problems faced by Ukrainian companies during the implementation of ESG criteria in their activities are highlighted, in particular: limited awareness and lack of understanding of ESG issues, lack of standardized ESG reporting, improper disclosure of ESG information, weak compliance with existing regulations, insufficient coverage of ESG issues in mass media information, etc. This article also suggests some measures that should be taken to solve the mentioned problems. The paper highlights the relationship between sustainability and financial performance, a widely debated topic. Some argue that implementing sustainability practices can have a positive impact on a company's financial performance in the long term, while others argue that sustainability practices can have a negative short-term impact on financial performance. In addition, the analysis of major meta-reviews that analyze and summarize research findings on the relationship between ESG reporting and financial performance is highlighted. These meta-reviews show that there is indeed a positive relationship between these metrics, although the strength of the relationship may vary depending on a number of factors, including industry, geographic location, and company size.